An analysis of Khawaja Mir Dard’s Poetry, in the Context of Pederasty - Khan, Shaista Hameed; Hasan, Ali; Bhatti, Muhammad Rafique (sourcecoder, 2023)
Khawaja Mir Dard is a Sufi poet، and this cannot be denied. But to make Sufism so dominant that the other themes of his poetry go into the background is not correct. The same attitude is taken with him regarding the subject of pederasty in his poetry. In his poetry, the words like “Khob Roo”, “Sanam”, “Larka”, “Pyara”, “Yar”, “Shokh”, “Stamgar”, “Messiah Nafs” and “Khat (beard)” are witnesses to the fact that the theme of pederasty is present in the poetry of Khawaja Mir Dard. This also proves that the power behind the poems based on pederasty, written by Khawaja Mir Dard, was Shahid Bazi, not Sufism.